MEWARISKAN IMAN DAN NILAI-NILAI KRISTIANI KEPADA GENERASI MUDA - Alexius Dwi Widiatna (Bahasa Indonesia, 2022)
The church has the responsibility to pass on the Christian faith and values to the youth of the church. Meanwhile, the development of technology and information has had a tremendous impact on the lives of young people, which is not always positive for the development of faith. There is a negative impact that the Catholic Church has to face on its youth. The Church faces a difficult challenge in passing on the faith to its youth, because the Church's proclamation is no longer attractive to young people, the digital generation. This study was conducted by studying literature from various sources in this digital era. Based on the literature study and observations, the author concludes that in order to inherit catholic faith to young people, the Church must understand the characteristics of the younger generation. Then, the pastoral minister needs to accompany the youth to walk together, using social media to proclam their faith and involving them in the church tasks and missions